Habituasi dan Perilaku Sosial Pelajar di Daerah Prostitusi Tegal Panas Kabupaten Semarang - Andwian Ody Prayoga; Sucihatiningsih Dian Wisika Prajanti (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Prostitution is a social problem that impacts all aspects of life. Students living in the Tegal Panas red-light district are distracted by negative behavior, thus hindering their moral development. This study aims to describe the habits and social behavior of students living in the Tegal Panas red-light district. This study uses a qualitative descriptive approach with a phenomenological research design. Data collection techniques include in-depth interviews, observation, and documentation. Data analysis uses Miles and Huberman, which consists of data collection, data condensation, data presentation, and conclusions. The results show that students' habits are influenced by the implementation of rules in the family environment, but interaction with teenagers and adults is unavoidable, which also influences their habits. Students' social behavior is more focused than teenagers who do not continue their education because they spend their time at school. However, some students also exhibit deviant social behavior such as rude language, smoking, drinking alcohol, engaging in casual sex and getting pregnant outside of marriage. This study recommends that parents and related social institutions take efforts to strengthen the morals of teenagers living in vulnerable areas, such as red-light districts.